Changes in lipid, fatty acids and phospholipids composition of whole rice bran after solid-state fungal fermentation - Melissa dos Santos Oliveira; Vivian Feddern; Larine Kupski; Eliane Pereira Cipolatti; Eliana Badiale‐Furlong; Leonor Almeida de Souza-Soares (2011)
The aim of this study was to evaluate fermented rice bran phospholipids, lipids and fatty acid content in a fermentation solid system with Rhizopus oryzae fungus. For this, aliquots were withdrawn every 24h over 120 h. The content of phospholipids was determined by colorimetric method. Esterified fatty acids were separated by gas chromatography, then identified and quantified. The total lipids from fermented rice bran (FB) decreased from 20.4% to 11.2% in the range between 0 h and 120 h of fermentation while phospholipid contents were increased up to 2.4 mg P g(lipid)(-1). In fermented bran, oleic, palmitic and linoleic acids prevailed, with a decrease in saturated fatty acids (20%) and increase in the unsaturated ones (5%). This study showed that rice bran fermentation with R. oryzae can be applied to the production of phospholipids altering the saturated to unsaturated fatty acid ratio.